The Effectiveness of Psychosocial, Psychological, and Psychoeducational Interventions for Women to Reduce Perinatal Depression in Low- and Middle-Income Countries: A Systematic Review and Meta-Analysis PROTOCOL - Berglund, Mari; Santcliments, Jana Riu; Sourander, Andre; Lahti, Mari (Gavin Publishers, 2025)
Background: The most common mental health condition that affects perinatal women and mothers worldwide is depression. Systematic reviews have been done to assess psychosocial, psychological, and psychoeducational interventions for depression during the perinatal period. However, most of them only include high income countries. The aim of this systematic review and meta-analysis is to synthesize and evaluate all the available evidence related to the effectiveness of these interventions of perinatal women with depressive symptoms in low- and middle-income countries. Methods and analysis: A systematic review and meta-analysis is going to be conducted on the basis of the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols 2020 statement. Randomized controlled studies will be identified through PubMed, CINAHL, Web of Science, PsycINFO, Scopus, Cochrane Register of Controlled Trial, ClinicalTrials.gov and revise through grey literature. Bridging searches will be also conducted through the competition of the review and articles meeting inclusion criteria will be added. Results will, where possible, be synthesized in statistical meta-analysis using Review Manager 5.4. Effect sizes expressed as odds ratio for categorical data and Standardized Mean Differences (SMD) for continuous data. The risk of bias is going to be assessed by The Cochrane Collaboration risk of bias tool. The standard χ2 and I2 tests will be used to quantify the amount of statistical heterogeneity. Sensitivity and subgroup analyses will be performed as well. Publication bias will be checked with funnel plots. Assuming included studies in the systematic review will be carried out with very different populations or types of interventions random effects model will be more conservative.